The first example we used was 4 3 7 x y x y in order

This preview shows page 34 - 39 out of 48 pages.

The first example we used was: 4 0 3 7 x y x y - = + = In order to be able to solve this system we have to rewrite the system in a way that y is expressed in terms of x in both equations, as follows: 4 0 4 3 7 7 3 x y y x x y y x - = = + = = - Now what we have to do is to plot these two graphs and their intersection should give us the solution to our problem. -10 -8 -6 -4 -2 0 2 4 6 8 10 -4 -2 0 2 4 6 8 10 12 14 4 y x = 7 3 y x = - (1,4)
Image of page 34

Subscribe to view the full document.

35 According to the plot of the two graphs the solution to our problem is 1 4 x and y = = , which is exactly what we got earlier. However, we must admit we have cheated a little bit by plotting the graphs using a mathematical software. However, imagine we have to plot these graphs by hand it will not be easy to get the exact solution, even with graphical papers sometimes. This is one drawback of using the graphical method to solve simultaneous equations. We can also try to solve our second problem by graphical method. 6 2 3 1 2 4 6 4 6 2 4 4 2 2 3 4 4 4 3 3 3 3 4 1 3 3 3 x y y x x y y x x x y y x y y x = - = - + = = - - - = ⇒ - = + = + = - - - -
Image of page 35